2001
DOI: 10.1155/s0161171201011085
|View full text |Cite
|
Sign up to set email alerts
|

A note on the countable union of prime submodules

Abstract: Abstract. Let M be a finitely-generated module over a Noetherian ring R. Suppose a is an ideal of R and let N = aM and, M is complete with respect to the b-adic topology, {P i } i≥1 is a countable family of prime submodules of M, and x ∈ M, then x + N ⊆ i≥1 P i implies that x + N ⊆ P j for some j ≥ 1. This extends a theorem of Sharp and Vámos concerning prime ideals to prime submodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…There are also the Sharp-Vamos prime avoidance theorems for noetherian complete local rings for countable prime ideals, stated as 16.7 A and 16.7 B in [4], see also [13], [10]. We have extended the latter result to complete noetherian semi-local rings in [8], for some purpose.…”
mentioning
confidence: 87%
“…There are also the Sharp-Vamos prime avoidance theorems for noetherian complete local rings for countable prime ideals, stated as 16.7 A and 16.7 B in [4], see also [13], [10]. We have extended the latter result to complete noetherian semi-local rings in [8], for some purpose.…”
mentioning
confidence: 87%
“…Details about -dim and width can be found in Roberts [2], Kirby [3], and Ooishi [4]; there is a general fact: for any Artinian -module width ≤ -dim < ∞ holds and is co-Cohen-Macaulay if and only if width = -dim holds (cf. [5][6][7]). Tang [8] has shown that if either ≤ 2 or is Cohen-Macaulay, then m ( ) is co-Cohen-Macaulay (see also [9]).…”
Section: Introductionmentioning
confidence: 99%